2022
DOI: 10.3389/fphar.2022.908783
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell-Related Gene Indicators in Pulmonary Hypertension

Abstract: Objective: Regulatory T cells (Tregs) are critical immune modulators to maintain immune homeostasis and limit pulmonary hypertension (PH). This study was aimed to identify Treg-related genes (TRGs) in PH.Methods: The gene expression profile from lungs of PH patients was retrieved from the Gene Expression Omnibus (GEO) database. The abundance of Tregs was estimated by the xCell algorithm, the correlation of which with differentially expressed genes (DEGs) was performed. DEGs with a |Pearson correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Immune infiltration analysis is to weigh the immune related genes in the gene expression matrix to get the activity status of related immune cells and pathways, which can be used to demonstrate relation of interested genes and immune status. The xCell R package was used to perform analysis, and P value < 0.05 was considered statistically significant ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Immune infiltration analysis is to weigh the immune related genes in the gene expression matrix to get the activity status of related immune cells and pathways, which can be used to demonstrate relation of interested genes and immune status. The xCell R package was used to perform analysis, and P value < 0.05 was considered statistically significant ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…They inhibit the activity of other T cells, especially CD8+ cytotoxic T cells, limit the immune response ( 39 ), reduce endothelial injury, and then impede PH-mediated vascular remodeling ( 40 , 41 ) by upregulating COX-2, PTGIS, HO-1, and PD-L1 in the media layer of the pulmonary arteriole ( 40 ). A previous study identified Treg-associated genes in the progression of PH, and the gene signature based on these genes was revealed to be a novel indicator to distinguish PH from controls ( 42 ). The imbalanced Th1/Th2 immune response has been considered central to the pathogenesis of PF ( 43 ); Treg impairment is also dedicated to the development of PF ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…previous study identified Treg-associated genes in the progression of PH, and the gene based on these genes was revealed to be a novel indicator to distinguish PH from controls (42). The imbalanced Th1/Th2 immune response has been considered central to the pathogenesis of PF ( 43 +CD25hiFoxp3+ Tregs has been shown in bleomycin-induced PF and other types of fibrosis animals (31), so the potential role of Tregs in PF remains uncertain and can be controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[76] The progression of PAH can be partly attributed to the reduced number and impaired function of Tregs. [77] In a Treg-deficient PAH model, females experienced more severe PAH than males, indicating that females rely more on Treg function to ameliorate pulmonary vascular damage in PAH. [78] Impaired Treg response can exacerbate inflammationmediated endothelial injury, leading to PAH.…”
Section: Pulmonary Arterial Hypertension (Pah)mentioning
confidence: 99%
“…By analyzing data from 62 patients with PAH, researchers found that Treg dysfunction occurs in all forms of PAH [76] . The progression of PAH can be partly attributed to the reduced number and impaired function of Tregs [77] . In a Treg-deficient PAH model, females experienced more severe PAH than males, indicating that females rely more on Treg function to ameliorate pulmonary vascular damage in PAH [78] …”
Section: Tregs and Progression Of Specific Cvdsmentioning
confidence: 99%